Effects of fabrication materials and methods on flexible resonant sensor signal quality. (November 2020) - Charkhabi, Sadaf; Chan, Yee Jher; Roy, Subhanwit; Islam, Md Monirul; Duffield, Brock B.; Jackson, Kyle J.; Bu, Lujia; Kim, Sang-Hwan; Hillier, Andrew C.; Neihart, Nathan M.; Reuel, Nigel F.
Abstract: Inductor–capacitor (LC) resonant sensors can provide low-cost, contactless measurement in closed environments. In this work, three fabrication methods to produce flexible LC sensors are compared: screen-printed pastes, etched copper-coated polyimide, and wound metal wires. The LC sensors were interrogated by near-field coupled antennas driven by a vector network analyzer. The sensor response was analyzed by extracting the resonant frequency (MHz) and the peak-to-peak amplitude (dB) of the S 21  scattering parameter. For screen-printed resonators, varying parameters such as print feature size (250 to 500 μ m ), conductive paste silver content (DuPont PE825 and 5028 for low and high silver content, respectively), curing condition (convection oven temperature and curing time), and paste viscosity (7.20–20.05​ Pa ⋅ s) were explored. An empirical model was fit to this data to allow for prediction of required sensor line thickness needed to meet an application's required step-off distance. The screen-printed resonant sensors were then compared to copper-etched and wound metal wires to evaluate the cost and performance tradeoff of the three fabrication approaches. Finally, a use case of the flexible, screen-printed resonant sensors was demonstrated by contact-free measurement of fluid level of in a closed, curved container.